Membrane-type 1 matrix metalloproteinase cleaves CD44 and promotes cell migration. - Kajita, M; Itoh, Y; Chiba, T; Mori, H; Okada, A; Kinoh, H; Seiki, M (2001)
Migratory cells including invasive tumor cells frequently express CD44, a major receptor for hyaluronan and membrane-type 1 matrix metalloproteinase (MT1-MMP) that degrades extracellular matrix at the pericellular region. In this study, we demonstrate that MT1-MMP acts as a processing enzyme for CD44H, releasing it into the medium as a soluble 70-kD fragment. Furthermore, this processing event stimulates cell motility; however, expression of either CD44H or MT1-MMP alone did not stimulate cell motility. Coexpression of MT1-MMP and mutant CD44H lacking the MT1-MMP-processing site did not result in shedding and did not promote cell migration, suggesting that the processing of CD44H by MT1-MMP is critical in the migratory stimulation. Moreover, expression of the mutant CD44H inhibited the cell migration promoted by CD44H and MT1-MMP in a dominant-negative manner. The pancreatic tumor cell line, MIA PaCa-2, was found to shed the 70-kD CD44H fragment in a MT1-MMP-dependent manner. Expression of the mutant CD44H in the cells as well as MMP inhibitor treatment effectively inhibited the migration, suggesting that MIA PaCa-2 cells indeed use the CD44H and MT1-MMP as migratory devices. These findings revealed a novel interaction of the two molecules that have each been implicated in tumor cell migration and invasion.